Neurotransmitter and Intestinal Interactions: Focus on the Microbiota-Gut-Brain Axis in Irritable Bowel Syndrome - Chen, Minjia; Ruan, Guangcong; Chen, Lu; Ying, Senhong; Li, Guanhu; Xu, Fenghua; Xiao, Zhifeng; Tian, Yuting; Lv, Linling; Ping, Yi; Cheng, Yi; Wei, Yanling (Frontiers in Endocrinology, 2022)
Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder of unknown etiology. The Gut-brain axis plays a central role in irritable bowel syndrome. The microbiota-gut-brain axis was proposed as a key regulator in IBS, considering the pivotal role of gut microbiota in maintaining local and systemic homeostasis. Recent studies demonstrated that neurotransmitters affect blood flow regulation, as well as intestinal motility, nutrient absorption, the gastrointestinal immune system, and microbiota. It Plays a potential role in the pathophysiology between the gastrointestinal system and the central nervous system. In this review, we mainly discuss the effects of the key neurotransmitters, such as 5-hydroxytryptamine, Dopamine, γ-aminobutyric acid, and Histamine, and their receptor activation along the microbiota-gut-brain axis on IBS, especially in visceral sensitivity and gastrointestinal motility. Researches in this field shed light on revealing the mechanism that neurotransmitters act in the pathogenesis of IBS, and discovering new therapeutic strategies based on traditional pharmacological approaches that target the nervous system or by novel therapies that target microbiota.